Continuous innovative practises and operational performance. (3rd November 2008) - Laugen, Bjorge Timenes; Boer, Harry
Most contributions in the fields of strategic management, operations strategy, organisation and innovation theory, do not provide knowledge on how to pursue the combination of exploration and exploitation excellence. This paper investigates the impact of change initiatives in high performance companies, and the effects of organisational formalisation and centralisation on the time and timeliness performance of new product development projects. We analyse data collected through two multinational surveys of manufacturing companies and case studies of two manufacturing companies. The findings indicate that companies with a high degree of improvement in exploitation and exploration performance differ from low performers in terms of the width and depth of the implementation of improvement activities. Furthermore, high performers are actively aware of configurational effects. Formalisation does not only lead to a longer lead-time of radical innovation but also, contrary to what theory suggests, of incremental innovations. Centralisation only affects the timeliness of NPD projects.